PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT CACAT TERSEMBUNYI PADA MOBIL PRODUKSI PRODUSEN OTOMOTIF - Shafa Atthiyyah Raihana, (2022)
This thesis discusses about case of dysfunctionality that can be found in the form of hidden defects in products produced by automotive manufactures, which causes losses to consumers. The purpose of this study is to examine the legal protection of consumers related to hidden defects in cars produced by automotive manufactures and the responsibility of automative manufactures for hidden defects in cars that have been produced and marketed by the public. The method used in this study is in the form normative juridicals, which is a legal research method carried out by examining library materials and secondary data including primary legal sources and secondary sources. The result of this study is the exposure of legal protection in Indonesia to consumers who are harmed by the findings of hidden defect in the vehicle they have bought from and authorized dealer that commonly authorized under the same company of manufactures. Therefore, the liability would also be taken by automotive manufactures due to losses suffered by consumers for their mistakes during the production of the vehicle. Automotive manufactures are expected to compensate for losses suffered by consumers and in the future pay attention to detailed product quality standards and product designs that will be issued so that there will be no other hidden defects in the future.